Can preoperative cervical spinal diffusion tensor imaging (DTI) indices predict surgical outcomes in patients with Hirayama disease? A retrospective cohort study - Gao, Yuan; Sun, Chi; Zhou, Shuyi; Ma, Xiaosheng; Xia, Xinlei; Lu, Feizhou; Zhang, Jun; Wang, Hongli; Jiang, Jianyuan (Frontiers in Neurology, 2022)
Abstract Objective Anterior cervical discectomy and fusion（ACDF）surgery can effectively prevent disease progression in patients with Hirayama disease and DTI can quantitatively assess spinal cord function. This study aimed to evaluate the relationship between preoperative spinal DTI indexes and outcomes in patients with Hirayama disease treated by ACDF. Methods We retrospectively analyzed forty-one HD patients treated by ACDF. DTI indexes including FA values and ADC values when patients in flexion position and neutral position were collected before surgery. Patients were divided into 2 groups according to the Odom score, and the difference in surgical outcomes between the two groups was confirmed by the quick disabilities of the arm, shoulder and hand (Q-DASH) scores. The DTI indexes in two groups of patients were compared. ROC curves and AUCs were used to evaluate the prediction value. The correlation between Q-DASH scores and DTI indexes was tested. Results The DTI indexes in two groups of patients were statistically significantly different in the cervical flexion position and the different segments were mainly located in the lower cervical spinal cord. The ROC curve of the DTI indexes in lower cervical spinal cord obtained an AUC greater than 0.7. Q-DASH scores were significantly correlated with DTI indexes in flexion position. Conclusion preoperative DTI indexes of spinal cord, especially the indexes of lower cervical spinal cord when patients in flexion position, can predict HD patients’ surgical outcomes. In general, a larger FA value and a smaller ADC value indicate a better surgical outcome.